2019
DOI: 10.1021/acs.jced.8b00589
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Study of Binary Systems of tert-Amyl Methyl Ether with n-Hexane and m-Xylene

Abstract: This work presents the experimentally determined density (ρ), viscosity (η), speed of sound (u), and surface tension (σ) data for tert-amyl methyl ether (TAME) + n-hexane and TAME + m-xylene systems at several temperatures (298.15, 308.15, 318.15, 323.15, and 328.15 K). These experimentally determined thermophysical data are utilized to compute various excess/deviation parameters such as molar volume (V E ), isentropic compressibility (κ s E ), speed of sound (u E ), deviation in viscosity (Δ ln η), isobaric t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…In general, n > 1 provided that the sorption is favourable; whereas, n < 1 demonstrates that the sorption process is chemical in nature. [61] In this study, the value found for n is equal to 1.78, which proves that the sorption is favourable and the process is physical in nature. Temkin isotherm Table 3 indicates the presence of low regression coefficient (0.94), demonstrating that the data of equilibrium isotherm of MV onto AP-Iva is poorly described by the Temkin model.…”
Section: Langmuir Isothermsupporting
confidence: 53%
“…In general, n > 1 provided that the sorption is favourable; whereas, n < 1 demonstrates that the sorption process is chemical in nature. [61] In this study, the value found for n is equal to 1.78, which proves that the sorption is favourable and the process is physical in nature. Temkin isotherm Table 3 indicates the presence of low regression coefficient (0.94), demonstrating that the data of equilibrium isotherm of MV onto AP-Iva is poorly described by the Temkin model.…”
Section: Langmuir Isothermsupporting
confidence: 53%
“… 10 , 28 Similarly, the knowledge of vapor–liquid equilibrium properties and surface tension of n -alkanes and alcohols is also required to study additives commonly used in fuels. 13 15 , 29 , 30 …”
Section: Introductionmentioning
confidence: 99%
“…10,28 Similarly, the knowledge of vapor−liquid equilibrium properties and surface tension of n-alkanes and alcohols is also required to study additives commonly used in fuels. [13][14][15]29,30 The surface tension of alkanes is also important in removing hydrocarbons from liquid effluents 31,32 and in the study of carbon dioxide capture and storage technologies. 18,33−35 In this last case, high pressures and temperatures are needed, which are not always easily accessible.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations